Bridging Indonesian Cultures Through Islam Wasatiyyah: International Students' Insights on Religious Moderation in an Islamic Higher Education - Maulana, Muhamad; Suliyana; Muru’uah, Ulfia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2025)
Indonesia, as the world’s largest Muslim-majority country, has long promoted Wasatiyyah Islam as a fundamental principle for maintaining religious harmony. This study explores the perceptions and experiences of international students within Indonesian Islamic higher education institutions (IHEIs) regarding religious moderation. Using a qualitative phenomenological approach, semi-structured interviews were conducted with five international students from diverse cultural and religious backgrounds. The findings indicate that many students were unfamiliar with Wasatiyyah prior to studying in Indonesia; however, their immersion in academic and social life at IHEIs broadened their understanding of Islamic moderation beyond personal religiosity to include interfaith tolerance and intercultural dialogue. The study highlights the role of Wasatiyyah as a framework that integrates Islamic principles with local traditions to promote inclusivity and religious tolerance. Nevertheless, challenges such as cultural adaptation, language barriers, and varying degrees of institutional commitment to moderation persist. This research contributes to the global discourse on Islamic education by advocating for the integration of religious moderation principles in IHEIs to enhance interfaith and intercultural harmony at both local and international levels.